MUNICIPAL GOVERNANCE IN MODERN RUSSIA - German Vetrov; Ioulia Zaitseva (European Regional Science Association (ERSA), 2005)
The results of survey, Municipal Governance in Modern Russia, was conducted in 2003 – 2004 by the Institute for Urban Economics (IUE), are presented in the paper. The primary goal of the research is to take an inventory of the experience accumulated by the cities in the field of managing local development, focusing on such important parameters as local leaders' awareness of new management technologies and popularity of such technologies, activity of municipalities at inter-municipal level, technical equipment of administrations. The study of the present status of municipal governance in Russia is all the more important now, with the beginning of a critically new period in the development of Russian cities. Internal and external factors of various nature determine the beginning of this period. On the one hand, relative economic stability in the country and experience accumulated over the years enabled many cities to turn at last from current problems and institutional reforms to strategic planning of their development. On the other hand, the system of local self-governance itself is being transformed drastically by the state – both in terms of territorial organization and municipal powers and interaction between different levels of government. Further transformation is determined by the new version of the Federal Law, On the General Principles of the Organization of Local Self-Governance in the Russian Federation, passed on October 6, 2003 (#131-FZ). The law will fully come into force on January 1, 2006, but preparatory work is already under way in Russian regions. The following main conclusions can be drawn, based on the survey results. 1.New advanced technologies of municipal governance and instruments of socio-economic development have passed the phase of pilot implementation and are now being disseminated on a mass scale. 2.Network of inter-municipal contacts has become a reality and is functioning actively. 3.Computerization of local administrations and information access of city residents have reached a rather high level. 4.Local self-governments are still faced with their traditional problems, first of all, finances and personnel. 5.Population size is not a decisive factor in institutional development of Russian cities. 6.Almost all sample municipalities are familiar with the new version of the law, On the General Principles of the Organization of Local Self-Governance in the Russian Federation.
Keywords: 330